2019
DOI: 10.1186/s12905-019-0802-6
|View full text |Cite
|
Sign up to set email alerts
|

How gender and religion impact uptake of family planning: results from a qualitative study in Northwestern Tanzania

Abstract: Background Women in Tanzania report a high unmet need for both information about and access to family planning. Prior studies have demonstrated the complex and variable relationship between religious faith and beliefs about family planning in sub-Saharan Africa. We hypothesized that a major reason for the poor uptake of family planning in Tanzania is that women and their partners are uncertain about whether pregnancy prevention is compatible with their religious beliefs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
92
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 25 publications
12
92
2
Order By: Relevance
“…In instances when side effects presented, these leaders interpreted it as a punishment from God and only discontinuing it would be the way to relief and freedom. Other studies found similar ndings and as discontinuation of any methods were linked to perceived comfort, often times such false narratives were accepted as truth [16,17] Furthermore, the discussions brought light to the fact that spousal miscommunication, unbalanced power and gender roles and non-involvement of male in family planning awareness program hinder the success of family planning interventions. This is underlined by cultural norms in favour of large families and patriarchal society where family planning decisions must be approved by men considered as head of the family but the latter has limited knowledge in the subject matter as family planning is known to be a "women thing".…”
Section: Discussionmentioning
confidence: 73%
“…In instances when side effects presented, these leaders interpreted it as a punishment from God and only discontinuing it would be the way to relief and freedom. Other studies found similar ndings and as discontinuation of any methods were linked to perceived comfort, often times such false narratives were accepted as truth [16,17] Furthermore, the discussions brought light to the fact that spousal miscommunication, unbalanced power and gender roles and non-involvement of male in family planning awareness program hinder the success of family planning interventions. This is underlined by cultural norms in favour of large families and patriarchal society where family planning decisions must be approved by men considered as head of the family but the latter has limited knowledge in the subject matter as family planning is known to be a "women thing".…”
Section: Discussionmentioning
confidence: 73%
“…We sought to use this established methodology to increase uptake of FP. In focus group discussions with Protestant church attenders, many men and women were unsure whether planning their families was compatible with their faith 6. Further, we reported that gender dynamics strongly impact a person’s uptake of FP and that despite misgivings about FP, focus group participants often noted its economic and maternal/child health benefits 6…”
Section: Introductionmentioning
confidence: 92%
“…Our study had three key goals. First, we further analysed prior data from focus group discussions6 with predominantly Protestant church attenders to construct a theoretical framework for understanding the multidimensional factors impacting the decision to use FP. Second, based on identified interpersonal and intrapersonal barriers to FP, we designed an educational seminar for church leaders.…”
Section: Introductionmentioning
confidence: 99%
“…In instances when side effects presented, these leaders interpreted it as a punishment from God and only discontinuing it would be the way to relief and freedom. Other studies found similar findings and as discontinuation of any methods were linked to perceived comfort, often times such false narratives were accepted as truth [16,17] Furthermore, the discussions brought light to the fact that spousal miscommunication and noninvolvement of male in family planning awareness program hinder the success of family planning interventions. This is underlined by cultural norms in favour of large families and patriarchal society where family planning decisions must be approved by men considered as head of the family but the latter has limited knowledge in the subject matter as family planning is known to be a "women thing".…”
Section: Discussionmentioning
confidence: 67%